Stratigraphy and rock magnetism in a profile at arroyo Tapalqué, Quaternary of Buenos Aires province: Palaeoenvironmental and palaeoclimatic implications - Orgeira, M.J. (2001)
In the right bank of the Arroyo Tapalqué (Salto de Piedra, Olavarría, Buenos Aires province) is a section through fluvial sediments of the Luján Formation (upper and lower members) and aeolian deposits of La Postrera Formation. A geological and geophysical study was carried out to determination the magnetic parameters of the sediments of both formations, in order to evaluate the environmental and climatic conditions at the time of deposition. Levels with high concentrations of ferromagnetic minerals are thought to be related to an increase in capacity of river transport probably due to higher rainfall. By contrast, a particular magnetic behaviour was detected in levels closely associated with pedogenetic processes (Suelo Puesto Callejón Viejo, SPCV, Suelo Puesto Berrondo, SPB and present soils). This behaviour is attributed to the partial dissolution of the ferromagnetic fraction (magnetic/titanomagnetite) and to possible formation of a high c oercitivity magnetic fraction (hematite?) as an associated process. These results are similar to those obtained for paleosols from the Buenos Aires Formation, probably because of parental material common to both. On the basis of present field and laboratory observations, together with previously available information, a detailed correlation is proposed between features observed in this section and palaeoclimatic fluctuations identified for Pleistocene/Holocene.